2005
DOI: 10.1103/physrevlett.94.056402
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Critical Scaling and the Origin of Non-Fermi-Liquid Behavior inSc1xUxPd

Abstract: We used inelastic neutron scattering to study magnetic excitations of Sc1-xUxPd3 for U concentrations (x=0.25, 0.35) near the spin glass quantum critical point (QCP). The excitations are spatially incoherent, broad in energy (E=variant Planck's over 2piomega), and follow omega/T scaling at all wave vectors investigated. Since similar omega/T scaling has been observed for UCu5-xPdx and CeCu6-xAux near the antiferromagnetic QCP, we argue that the observed non-Fermi-liquid behavior in these f-electron materials a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…39͒ and in certain spin-glass QCP heavy Fermion systems. 26,27 Although there is at present no comprehensive theory for the expected properties of a metallic spin-glass QCP, the reduced magnetic transition temperature and the continuous nature of the transition ͓Fig. 2͑c͔͒ imply that the scaling behavior in the T c = 23 K PLCCO should persist down to lower energies and temperatures than that of the T c = 21 K sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39͒ and in certain spin-glass QCP heavy Fermion systems. 26,27 Although there is at present no comprehensive theory for the expected properties of a metallic spin-glass QCP, the reduced magnetic transition temperature and the continuous nature of the transition ͓Fig. 2͑c͔͒ imply that the scaling behavior in the T c = 23 K PLCCO should persist down to lower energies and temperatures than that of the T c = 21 K sample.…”
Section: Discussionmentioning
confidence: 99%
“…As AF order is suppressed in the system, the low-energy excitations transform from regimes coupled to the onset of the AF phase into a virtually temperature-independent regime similar to those observed in several heavy Fermion systems known to be near a quantum critical point ͑QCP͒ in the phase diagram. [25][26][27][28] In Sec. VII, we discuss the applicability of quantum critical scaling in describing the spin dynamics of PLCCO with different transition temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Mutually similar behavior of the curves measured at different temperatures suggests a common scaling. The literature data available for a few quantum-critical NFL systems [13][14][15][16][17][18][19][20][21] indicate that the imaginary part of the dynamical susceptibility χ (ω,T ) follows a scaling relation and Z(hω/T ) is a scaling function specific for both given compound and underlying QCP mechanism. In particular, Aronson et al 13 have used…”
Section: Resultsmentioning
confidence: 99%
“…Inelastic neutron scattering experiments on Sc 1−x U x Pd 3 [61] reveal excitations in the x = 0.35 compound that are broad in energy ω, T -independent, and wave vector q-independent, and consistent with a single-ion scenario. Furthermore, the imaginary part of the dynamical susceptibility χ (q, ω, T ) scales with ω/T for all values of q, ω, and T studied with a scaling exponent α = 1/5, indicating that temperature is the only relevant energy scale.…”
Section: Y 1−x U X Pdmentioning
confidence: 95%
“…The case for NFL behavior was strengthened by a subsequent inelastic neutron scattering study, which found energy-temperature (ω/T ) scaling in the dynamic magnetic susceptibility [120]. The significance of this behavior, identified in varied NFL materials like UCu 5−x Pd x [62]and Sc 1−x U x Pd 3 [61], is that the temperature itself acts like the energy scale in the system, as would happen in the absence of an effective Fermi energy. Also, the scaling exponents determined from ω/T scaling agree with the NFL exponents from the power-law T dependence in bulk χ(T ).…”
Section: Uru 2 Simentioning
confidence: 97%